Hemodiafiltration - Ronco, Claudio 1951-; Canaud, Bernard; Aljama, Pedro (Contributions to nephrology, 2008)
The application of hemodiafiltration has been restricted until recently, when a broader clinical application has been made possible due to evidence from large studies and clinical investigations. This book provides an updated review of the evolution, advances and recent results achieved by hemodiafiltration in the clinical arena. The first part is devoted to historical notes and an outline of the evolution of different forms of hemodiafiltration, made possible by technological developments in the fields of membranes, machines and fluids. The next section describes the theoretical rationale for hemodiafiltration, providing a detailed analysis of the involved mass separation processes, the hydraulic properties of the dialyzers, fluid mechanics and crossfiltration in hollow fiber hemodialyzers. An outline of different hemodiafiltration techniques, also reporting peculiar transport mechanisms and related technology, is given next, and a section on the clinical effects of hemodiafiltration concludes this book.Including different technologies, the publication offers a complete overview of the technical and clinical possibilities provided by hemodiafiltration in its widest concept, ranging from the molecular basis to the most practical application. It will be a valuable tool for the implementation of hemodiafiltration in daily practice aimed at beginners and experts, scientists and physicians, students and senior faculty members alike